Bilateral Breast Geometry Analysis –A Preliminary Tool for Detection of Breast Abnormality - Bebina, Hidangmayum; Shivaram, Joshi Manisha; Katke, Aradhana; Umadevi, V (International Journal of Computer Sciences and Engineering, 2019)
With the increase in the mortality rate due to Breast cancer among young women folks, different techniques are developed for the early detection of breast abnormality. Thermal Infrared Imaging is one such modality that made use of thermal camera for the detection of the dreadful disease. This research work presents the use of bilateral breast geometrical analysis on the breast thermal signatures collected from Kidwai Institute of Oncology, Bangalore. The analysis has been performed on 70 bilateral breast thermal signatures. Breast thermal signatures have been captured at distances 1m, 1.5m and less than 1.5m. An algorithm has been implemented based on Digital Image Processing techniques. ROI processing has been performed on suitable palette. After detecting contour of breast area, edge linking has been implemented using Parabolic Hough Transform. Obtained results are correlated with ground truth mammography reports. It has been observed that out of 70 bilateral images, 21 have shown asymmetry which matches with ground truth. The analysis gives 77% sensitivity and 60.4% specificity. The distance between subject and camera also shows the effect on sensitivity. It is observed that the images taken at 1.5m distance are more apt for analysis purpose.